Development of thermoultrasound assisted blanching to improve enzyme inactivation efficiency, drying characteristics, energy consumption, and physiochemical properties of sweet potatoes - Huihuang Xu; Yaru Guan; Chun Shan; Wanru Xiao; Min Wu (Ultrasonics Sonochemistry, 2023)
Thermoultrasound (USB) as a promising alternative to traditional hot water (HWB) blanching was employed to blanch sweet potatoes and its influence on enzyme activity, drying behavior, energy consumption and physiochemical properties of sweet potatoes were investigated. Results showed that successive increases in blanching temperature and time resulted in significant (p < 0.05) decreases in PPO and POD activities. Compared to HWB, USB led to more effective drying by promoting texture softening, moisture diffusion, microstructure alterations, and microchannels formation, which significantly reduced energy consumption and improved the overall quality of the dried sample. Specifically, USB at 65 °C for 15 min improved water holding capacity and ABTS, while USB at 65 °C for 30 min improved color (more red and yellow), total phenolic content, total carotenoid content, and DPPH. Unfortunately, blanching process showed detrimental effects on the amino acid composition of dried samples. Overall, the development of thermoultrasound assisted blanching for sweet potatoes has the potential to revolutionize the processing and production of high-quality sweet potato products, while also improving the sustainability of food processing operations.